IT synergy in the application of Technological Pedagogical Content Knowledge (TPACK) in the social studies learning process: A literature study - Wijanarko, Anggit Wahyu; Amania, Yuliani Hidayatul; Sariyatun, Sariyatun; Ramadan, Syahri (Program Pascasarjana Universitas Negeri Yogyakarta, 2022)
This research is motivated by the increasing need for Information and Technology (IT) in the field of education in the era of globalization. The advancement of IT in the era of globalization requires humans to have superior IT skills. One way to synergize IT to provide superior IT skills is through education. Education is the right field in synergizing IT, especially in the learning process with the Technological Pedagogical Content Knowledge (TPACK.) approach. The formulation and purpose of the research is to provide a descriptive analysis of the IT synergy with the TPACK approach in the social studies learning process at the Junior High School (SMP) level. This research uses descriptive analysis method with literature review from books, journal articles, and other sources related to the research topic. The benefits of this research are: (1) It can be used as a reference for similar research related to IT synergy with TPACK approach in other learning; (2) It can be used as an illustration of the application of IT synergy with TPACK approach in social studies learning process; and (3) It can be an inspiration for social studies teachers in conducting social studies learning by synergizing IT with TPACK approach in schools. This research not only fulfills an urgent need for a deeper understanding of how IT can collaborate with TPACK in social studies learning, but also aims to provide an important contribution to the development of effective learning practices in the future.